2000
DOI: 10.2337/diabetes.49.8.1359
|View full text |Cite
|
Sign up to set email alerts
|

Transient neonatal diabetes: widening the understanding of the etiopathogenesis of diabetes.

Abstract: Transient neonatal diabetes (TND) is a rare type of diabetes that presents soon after birth, resolves by 18 months, and predisposes to diabetes later in life. A total of 30 patients were ascertained and investigated for aberrations of chromosome 6. A genotype/phenotype study was also performed. Genotypically, these patients can be classified into 4 etiologic groups. Group 1 had paternal uniparental isodisomy of chromosome 6 (11 cases, including 1 set of identical twins). Group 2 had a duplication involving chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
201
0
21

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(225 citation statements)
references
References 34 publications
3
201
0
21
Order By: Relevance
“…Interestingly, it has also been suggested that this region on chromosome 6 contains a gene responsible for transient neonatal diabetes mellitus, which could also be a candidate gene for IDDM15 in this region. 200,201 A very recent report provides evidence for a locus in the immunoglobin heavy chain region on chromosome 14q32.3 producing susceptibility to T1D, 30 this locus has been designated IDDM16. Support for linkage was obtained in 351 North American and UK families (P = 0.002).…”
Section: Iddm2-the Insulin Gene (Ins) Regionmentioning
confidence: 99%
“…Interestingly, it has also been suggested that this region on chromosome 6 contains a gene responsible for transient neonatal diabetes mellitus, which could also be a candidate gene for IDDM15 in this region. 200,201 A very recent report provides evidence for a locus in the immunoglobin heavy chain region on chromosome 14q32.3 producing susceptibility to T1D, 30 this locus has been designated IDDM16. Support for linkage was obtained in 351 North American and UK families (P = 0.002).…”
Section: Iddm2-the Insulin Gene (Ins) Regionmentioning
confidence: 99%
“…Some of these mutations lead to a more severe syndrome in which developmental delay and epilepsy accompany neonatal diabetes, a condition known as DEND syndrome [9]. Mutations in KCNJ11 can also result in transient neonatal diabetes mellitus (TNDM) [14], although in most patients TNDM is caused by an abnormality of the imprinted region on chromosome 6q24 [15]. Kir6.2 associates with the sulphonylurea receptor SUR1 (ABCC8) to form the K ATP channel of the pancreatic beta cell [16,17] and mutations in ABCC8 can also cause neonatal diabetes [18].…”
Section: Introductionmentioning
confidence: 99%
“…The rarity of TNDM (1:200,000 to 1:400,000 live births) poses challenges for data collection about clinical features, outcome and management. Until now the clinical features of 6q24 TNDM have been defined in small case studies, some including patients without a molecularly confirmed diagnosis [6,7]; therefore trends in birthweights, presentation, remission and clinical features, particularly comparing different 6q24 TNDM aetiologies, has been limited by low statistical power. Here we describe the clinical presentation of the largest worldwide cohort of confirmed 6q24 TNDM cases, the majority of whom have not been previously reported, which enables us for the first time to quantify genotype-phenotype correlations.…”
mentioning
confidence: 99%